Stepwise assembly of functional C‐terminal REST/NRSF transcriptional repressor complexes as a drug target. (12th March 2017) - Inui, Ken; Zhao, Zongpei; Yuan, Juan; Jayaprakash, Sakthidasan; Le, Le T. M.; Drakulic, Srdja; Sander, Bjoern; Golas, Monika M.
Abstract: In human cells, thousands of predominantly neuronal genes are regulated by the repressor element 1 (RE1)‐silencing transcription factor/neuron‐restrictive silencer factor (REST/NRSF). REST/NRSF represses transcription of these genes in stem cells and non‐neuronal cells by tethering corepressor complexes. Aberrant REST/NRSF expression and intracellular localization are associated with cancer and neurodegeneration in humans. To date, detailed molecular analyses of REST/NRSF and its C‐terminal repressor complex have been hampered largely by the lack of sufficient amounts of purified REST/NRSF and its complexes. Therefore, the aim of this study was to express and purify human REST/NRSF and its C‐terminal interactors in a baculovirus multiprotein expression system as individual proteins and coexpressed complexes. All proteins were enriched in the nucleus, and REST/NRSF was isolated as a slower migrating form, characteristic of nuclear REST/NRSF in mammalian cells. Both REST/NRSF alone and its C‐terminal repressor complex were functionally active in histone deacetylation and histone demethylation and bound to RE1/neuron‐restrictive silencer element (NRSE) sites. Additionally, the mechanisms of inhibition of the small‐molecule drugs 4SC‐202 and SP2509 were analyzed. These drugs interfered with the viability of medulloblastoma cells, where REST/NRSF has been implicated in cancer pathogenesis. Thus, a resource for molecular REST/NRSF studies and drug development has been established.